Special Education Undergraduate Students Perspective towards the Importance of Malaysia Sign Language Learning - Rashid, Syar Meeze Mohd; Rashid, Syar Meeze Mohd; Yasin , Mohd Hanafi Mohd; @ Ashaari, Noraidah Sahari (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to identify the perspective of undergraduate students of Special Education on the importance of Malaysia sign language learning. The study involved the views and perspectives of 200 undergraduate students of Special Education at three public universities. These three Public Institutions of Higher Learning (IPTA) offer special education and sign language courses as one of the compulsory courses for students. This study was conducted by distributing questionnaires to students and analyzed using Packages for Social Sciences (SPSS) version 20.0. The results showed that all items achieved a high level of agreement with a mean score of 4.67 and standard deviation (SD) was 0.359. The highest mean values were shown and indicated that sign language enabled students to communicate with hearing-impaired students (mean = 4.74, SD = 0.359) in the third item. In addition, the second position indicated that sign language was a compulsory course for special education undergraduate students with a high level of agreement scores (mean = 4.72, SD = 0.450) on the second item. Therefore, the findings show that sign language learning is a very important skill that students need to acquire in order to become a versatile, skilled and quality special education teacher.